Wireless communications : algorithmic techniques - Vitetta, Giorgio (Chichester, West Sussex, United Kingdom : John Wiley & Sons Inc., 2013)
"This book introduces the theoretical elements at the basis of various classes of algorithms commonly employed in the physical layer (and, in part, in MAC layer) of wireless communications systems. It focuses on single user systems, so ignoring multiple access techniques. Moreover, emphasis is put on single-input single-output (SISO) systems, although some relevant topics about multiple-input multiple-output (MIMO) systems are also illustrated. Comprehensive wireless specific guide to algorithmic techniques Provides a detailed analysis of channel equalization and channel coding for wireless applications Unique conceptual approach focusing in single user systems Covers algebraic decoding, modulation techniques, channel coding and channel equalisation"--
Introduction -- Modulation and detection. Wireless channels -- Digital modulation techniques -- Detection of digital signals over wireless channels: decision rules -- Data-aided algorithms for channel estimation -- Detection of digital signals over wireless channels: channel equalization algorithms -- Information theory and coding schemes. Elements of information theory -- An introduction to channel coding techniques -- Classical coding schemes -- Modern coding schemes -- Signal space codes -- Combined equalization and decoding -- Appendix A: Fourier transforms -- Appendix B: Power spectral density of random processes -- Appendix C: Matrix theory -- Appendix D: Signal spaces -- Appendix E: Groups, finite fields and vector spaces -- Appendix F: Error function and related functions -- References -- Index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Wireless communication systems -- Mathematics; Algebra; TECHNOLOGY & ENGINEERING -- Telecommunications; Electronic books; Electronic books